Chain Mapping Tools for Analysis and Improvement of Inter-Organisational Information Systems and Relationships - Storer, Christine; Taylor, D. (Wageningen Academic Publishers, 2006)
It is argued there is a gap between existing "zero level" chain diagrams that only show organisations involved and detailed process mapping tools that are commonly used when analysing supply chains. To address this, a number of relationship mapping tools are presented. More detailed zero level maps are suggested to identify opportunities for improvement that may have the greatest strategic impact on the chain as well as to highlight likely obstacles to cooperation. Multiple level relationship diagrams are suggested to identify the departments and the organisational hierarchical levels involved in these interactions so a team to work on the problem or opportunity can be established. More detailed work can be facilitated with process diagrams.